2023
DOI: 10.56508/mhgcj.v6i1.150
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review to explore the effect of yoga on anxiety in adults

Abstract: Introduction: The National Health Service cannot chronically sustain the overwhelming demands being placed on it due to financial cuts, staff numbers and recent presence of Covid-19. As a result, anxiety levels are on the rise thus increasing the need for effective first-line treatment. Purpose: The purpose of this systematic review was to examine the efficacy of yoga as a first-line treatment for anxiety. Previous systematic reviews have produced mixed results. Methodology: The inclusion criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…( 51 ) suggested, the results of their meta-analyses are mixed and often inconclusive because of the lack of rigorous research designs. However, another systematic review ( 53 ) found that yoga was effective regardless of the sample size or research design. Importantly, unlike other meta-analyses, this review article excluded such search terms as depression because anxiety and depression are frequently comorbid and studied together.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 51 ) suggested, the results of their meta-analyses are mixed and often inconclusive because of the lack of rigorous research designs. However, another systematic review ( 53 ) found that yoga was effective regardless of the sample size or research design. Importantly, unlike other meta-analyses, this review article excluded such search terms as depression because anxiety and depression are frequently comorbid and studied together.…”
Section: Discussionmentioning
confidence: 99%
“…The credibility of the review by Laban-Sharman et al. ( 53 ) was increased by including studies with validated anxiety assessment scales, such as State–Trait Anxiety Inventory and similar rating scales. The only exception was a study by Simon et al.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to build bridges between Western and Buddhist psychology (Wallace & Shapiro, 2006) allowed the two systems to merge in the therapeutic arena (Shonin et al, 2014). Mindfulness, for instance, has shown e↵ects on the physiological correlates of psychological experiences (Gamaiunova et al, 2022;Morton et al, 2020), and has become a common tool in the therapeutic arsenal (Coelho et al, 2013;Gu et al, 2015;Kelly, 2023;Otani, 2023).A similar coalescence has occurred with yoga and psychotherapy (Laban-Sharman et al, 2023;Kang & Wittingham, 2010) in recent years. Yet modern psychology has remained visibly reluctant to consider ancient Eastern models of the mind in its theoretical development.…”
Section: The Way Aheadmentioning
confidence: 97%